Analisis Pertumbuhan Tinggi Badan dan Berat Badan Anak Pra Sekolah Umur 5-6 Tahun Di TK Dunia Anak Islam Makassar Banggai - badriani badawi (Jurnal Komunitas Kesehatan Masyarakat, 2022)
ABSTRACT In an effort to overcome malnutrition in children, including pre-school age children, the government plans to increase a balanced nutrition program and prepare a total budget of Rp. 60 trillion for 12 institutions involved in handling the nutritional status of children. This study aims to analyze the factors that influence differences in height and weight growth of pre-school age children. This type of quantitative research uses a cross sectional study approach. The subjects of this study were pre-school children aged 5-6 years in the Islamic Children's World Kindergarten. The sampling technique is a total sampling of 50 students. Collecting data by using a questionnaire. The results of the study for nutritional status obtained the chi square test test value with p-value = 0.000 with a significance level of = 0.05, which means the p<a value, thus Ho is rejected and Ha is accepted, which means there is an influence between nutritional status on height growth. body and weight of preschool-aged children in Islamic kindergarten world, then for nutrition p value = 0.002 with a significance level of = 0.05 which means p <α value, thus Ho is rejected and Ha is accepted which means there is an influence of nutrition on the growth of height and weight of preschool-aged children in the World Kindergarten for Islamic children in Makassar and for behavior, the value of p - value = 0.000 is obtained with a significance level of = 0.05, which means the value of p < , thus Ho is rejected and Ha is accepted which means that This means that there is a significant effect between behavior and the growth of height and weight of preschool children aged 5-6 years at the World Islamic Children's Kindergarten in Makassar. There is an influence between nutritional status, nutrition, and behavior with the growth of height and weight of preschool aged children aged 5-6 years in the Makassar Islamic World Kindergarten (Ns. Arif Rohman Mansur, 2020)